On the so-called “myth of Sulla” (about the article by Alexandra Eckert) - Korolenkov, Anton Viktorovich; Chrustaljow, Wjatscheslaw Konstantinovich (Античный мир и археология, 2022)
The authors analyze Ugo Laffi’s and Francois Hinard’s conception of the “myth of Sulla” and its critics by Alexandra Eckert. Laffi attributes the appearance of Sulla’s image as the cruel tyrant (i.e. of the “myth of Sulla”) to Caesar’s dictatorship, while in Hinard’s opinion it happened later, during Augustan principate. However, Eckert argues that Sulla had the reputation of a cruel tyrant even in his lifetime. The authors agree with Eckert, but make important corrections and additions to her argumentation.